THE EFFECT OF COMPLEMENTARY BACK MASSAGE THERAPY ON BLOOD PRESSURE IN ELDERLY WITH HYPERTENSION - Anggraini, Rista Dian; Hidayah, Ardiyanti; Farida, Siti Nur (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2024)
Background: According to the World Health Organization, hypertension is a condition where the blood vessels have high blood pressure (systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥ 90 mmHg). Hypertension in the elderly is differentiated into hypertension where the systolic pressure is equal to or greater than 140 mmHg and/or diastolic pressure is equal to or greater than 90 mmHg, as well as isolated systolic hypertension where the systolic pressure is greater than 160 mmHg and the diastolic pressure is lower than 90 mmHg (NOC, 2015). Objectives: This study aimed to analyze the effect of complementary back massage therapy on blood pressure in elderly people with hypertension. Design: The research design used a quasi-experiment with a pretest-posttest control group design approach. Methods: This research was carried out from April to October 2023 at the Posyandu for the Elderly in Candimulyo Village, Jombang Regency. The population in this study were all elderly people who attended the Posyandu for the Elderly in Candimulyo Village, Jombang Regency. The sampling technique used in this research is purposive sampling, by establishing several criteria. The sample size for each group was 20 respondents. The research data were analyzed using the Wilcoxon and Mann-Whitney tests. Results: The Wilcoxon test showed that there was a significant difference in blood pressure in the treatment groups with the systole p-value being 0.000, the diastole p-value 0.025. There was no significant difference in blood pressure in the control group, both in systole with a p-value of 0.086 and a diastole p-value of 0.140. There is a significant effect of complementary back massage therapy on systolic blood pressure with a p-value of 0.000 and a diastolic p-value of 0.028. Conclusion: Based on the results of this research, back massage therapy is recommended as a non-pharmacological therapy to stabilize blood pressure and prevent cardiovascular complications in the elderly.